Heavy Metal Content and Health Risk Assessment of Some Selected Medicinal Plants from Obuasi, a Mining Town in Ghana - Flora Amerley Amarh; Eric Selorm Agorku; Ray Bright Voegborlo; Gerheart Winfred Ashong; Enoch Nii Klu Nortey; Napoleon Jackson Mensah (Journal of Chemistry)
Medicinal plants represent an important class of traditional medicines. This research was conducted to assess the levels of selected heavy metals in some medicinal plants from Obuasi, a mining area in Ghana. Twenty different medicinal crops were sampled for this study. The levels of arsenic (As), cadmium (Cd), chromium (Cr), mercury (Hg), manganese (Mn), nickel (Ni), and lead (Pb) were determined by inductively coupled plasma mass spectroscopy (ICP-MS) after wet digestion. The concentrations (mg/kg) of As, Cd, Cr, Hg, Mn, Ni, and Pb were 1.092 − 0.206, 1.341 − 0.253, 6.603 − 2.005, 0.045 − 0.001, 282.798 − 20.583, 4.967 − 1.676, and 26.410 − 0.629, respectively. Some concentrations of Cr, Cd, As, Mn, and Pb analyzed in all 20 medicinal plant samples exceeded WHO permissible limits for medicinal food while concentrations of Ni, As, and Hg for all the samples were below the WHO permissible limit. The estimated dietary intake (EDI) was compared to the tolerable daily intake recommended by WHO/FAO. Results obtained from hazard indices such as the hazard quotient and carcinogenic risk show that the medicinal plants are not likely to cause cancer if they are consumed over a prolonged period of time.